Deposition of stainless steel thin films: an electron beam physical vapour deposition approach - Ali, Naser; Teixeira, Joao Amaral; Addali, Abdulmajid; Saeed, Maryam; Al-Zubi, Feras; Sedaghat, Ahmad; Bahzad, Husain (MDPI, 2019)
This study demonstrates an electron beam physical vapour deposition approach as an alternative stainless steel thin films fabrication method with controlled layer thickness and uniform particles distribution capability. The films were fabricated at a range of starting electron beam power percentages of 3–10%, and thickness of 50–150 nm. Surface topography and wettability analysis of the samples were investigated to observe the changes in surface microstructure and the contact angle behaviour of 20 °C to 60 °C deionised waters, of pH 4, pH 7, and pH 9, with the as-prepared surfaces. The results indicated that films fabricated at low controlled deposition rates provided uniform particles distribution and had the closest elemental percentages to stainless steel 316L and that increasing the deposition thickness caused the surface roughness to reduce by 38%. Surface wettability behaviour, in general, showed that the surface hydrophobic nature tends to weaken with the increase in temperature of the three examined fluids.
Keywords: coating; controlled deposition rate; EB-PVD; morphology; topography; wettability